Detection of Nosocomial Respiratory Infections among Hospitalized Patients in Intensive Care Unit: a Survey in Northern Iran - Mahshid Saeedi1; Leila Fozouni1* (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Nosocomial respiratory infections are a significant cause of mortality in hospitalized patients in Middle East countries. This study assesses the prevalence of nosocomial respiratory infection and associated factors as a tool for early diagnosis among intensive care unit (ICU) patients at risk for mortality. Methods: From January to November 2021, 357 patients with more than 72 h hospitalization in ICU were monitored. Respiratory samples were examined for the presence of microbial isolates using clinical microbiology procedures based upon microscopic morphology, cultural and PCR methods. Demographic data were collected, including age, gender, date of hospitalization, underlying diseases, date of death, and laboratory data. Results: Out of fiftythree positive cultures, 18 samples (34%) were positive for fungal isolates, and the rest were positive for bacterial isolates. The most common bacterial and fungal isolates were Streptococcus pyogenes (17.9%) and Candida albicans (22.5%). Of the infected patients, 67.9% were male, 39.62 % had kidney diseases, and 15.09% died due to nosocomial infections. The results also showed that the tumor necrosis factor α and complement component 3 levels were significantly associated with the incidence of respiratory fungal or bacterial infections (P<0.05). Conclusions: The rate of respiratory nosocomial infection in ICU patients was high. It is essential to implement control measures such as managing the length of hospital stay and examining the patient's immune factors to reduce the risk of these infections in ICU patients. Also, ICU patients should be prescribed appropriate antibiotics to prevent respiratory infections.